Types of Diversity of Plants Standing of Pinus (Pinus Merkusii) In Uyem Beriring Natural Tourism, Gayo Lues District - Masyitah Masyitah; Djufri Djufri; Hasanuddin Hasanuddin; Muhibbuddin Muhibbuddin; Cut Nurmaliah (Jurnal Ilmiah Mahasiswa Pendidikan Biologi, 2022)
ABSTRACTThis study aims to determine the type and level of diversity (H') of plants. The research was conducted in August – September 2021. The approach used in this study was quantitative with a descriptive type of research. Data was collected by using the quadratic method with purposive sampling technique. The parameters observed included Absolute Frequency (FM), Absolute Density (KM), Absolute Dominance (DM), and the level of diversity (H'). The results obtained 136 species from 50 families consisting of tree habitus 12 species from 9 families, shrubs 55 species from 31 families, and herbs 69 species from 26 families. The understorey that dominates all stations is paitan grass (Axonopus compressus). The level of diversity of understorey species of pine stands in Uyem Beriring Nature Tourism, Gayo Lues Regency at station I there are 117 species with a diversity index of 4.27 which is categorized as very high. At station II there are 61 species with a diversity index of 3.72 and at station III there are 32 species with a diversity index of 3.23 which are categorized as high. The average level of plant diversity at the three stations is H' = 3.74, meaning that the diversity of plants in Uyem Beriring Nature Tourism, Gayo Lues District is relatively high.Keywords: Diversity, Pine, Undergrowth, Uyem Beriring. Penelitian ini bertujuan untuk mengetahui jenis tumbuhan bawah tegakan pinus (Pinus merkusii) di Wisata Alam Uyem Beriring Kabupaten Gayo Lues. Penelitian dilakukan pada bulan Agustus-September 2021. Pendekatan yang digunakan dalam penelitian ini adalah Pendekatan kuantitatif dengan jenis penelitian deskriptif. Pengumpulan data dilakukan mengunakan metode kuadrat dengan teknik Purposive Sampling. Parameter yang diamati meliputi Frekuensi Mutlak (FM), Kerapatan Mutlak (KM), Dominansi Mutlak (DM), dan Tingkat Keanekaragaman (H’). Hasil penelitian diperoleh 136 jenis dari 50 familia terdiri dari habitus pohon 12 jenis dari 9 familia, perdu 55 jenis dari 31 familia, dan herba 69 jenis dari 25 familia. Tumbuhan bawah yang mendominasi seluruh stasiun yaitu rumput paitan (Axonopus compressus). Keanekaragaman jenis tumbuhan bawah tegakan pinus (Pinus merkusii) di Wisata Alam Uyem Beriring Kabupaten Gayo Lues pada stasiun I terdapat 117 jenis dengan indeks keanekaragaman 4.27 (sangat tinggi). Pada stasiun II terdapat 61 jenis dengan indeks keanekaragaman 3.72 (tinggi), dan Pada stasiun III terdapat 32 jenis dengan indeks keanekaragaman 3.23 (tinggi). Rata-rata tingkat keanekaragaman tumbuhan pada ketiga stasiun adalah H’= 3,74, artinya keanekaragaman tumbuhan di Wisata Alam Uyem Beriring Kabupaten Gayo Lues tergolong tinggi.Kata Kunci : Keanekaragaman, Pinus, Tumbuhan Bawah, Uyem Beriring.